ANTAGONISM OF SOME WELL-KNOWN BIOAGENTS AGAINST CURVULARIA ERAGROSTIDIS (HENN.) J.A.MEY. - AN INCITANT OF SPIDER LILLY LEAF TIP BLIGHT - V. P. PRAJAPATI; D. M. JOSHI; N. K. GAJRE; S. S. KANSARA (The Bioscan, 2012)
Investigation on leaf tip blight (Curvularia eragrostidis (Henn.) J. A. Mey. of spider lilly (Hymenocallis littoralis L.) under south Gujarat conditions was carried out to find out suitable management strategies. Due to hazardous effect of chemical fungicides, search for safer alternative to control the pathogen is better choice. This led to trials on the use of bioagents to control the pathogen. The eight known bioagents were evaluated by dual culture, pathogen at periphery and pathogen at the centre technique to monitor antagonistic effect. The results revealed that out of all the eight bioagents used, three bioagents viz., T. viride (73.39 %, 69.80%, and 70.73% maximum growth inhibition in dual culture, pathogen at periphery and pathogen at the centre methods respectively), T. longibrachyatum (71.76%, 64.57% and 69.93% maximum growth inhibition in dual culture, pathogen at periphery and pathogen at the centre methods respectively) and T. harzianum (67.75%, 63.55% and 67.49% maximum growth inhibition in dual culture, pathogen at periphery and pathogen at the centre methods respectively) showed strong antagonistic effect to inhibit the mycelia growth of the pathogen significantly.